Cholera: Trends in the Development of the Epidemic Process in 2021, Forecast for 2022 - A. K. Noskov; V. D. Kruglikov; E. A. Moskvitina; E. V. Monakhova; L. V. Mironova; А. A. Kritsky; A. A. Lopatin; O. S. Chemisova; E. G. Soboleva; S. M. Ivanova; A. S. Vodop’yanov; S. I. Stenina; et al. (Проблемы особо опасных инфекций, 2022)
The aim of the work was to summarize the results of cholera monitoring in 2021, to assess current trends in the development of the epidemic process, and to predict the epidemiological situation in the Russian Federation for 2022. It was established that within the period of 2012–2021, 4117264 cases of cholera with the spread of infection across 83 countries on all continents were registered in the world and there was a downward trend in the incidence in Asia and Africa. The dynamics of monthly morbidity in 2021 was associated with emergencies as factors of epidemiological risk. Epidemics and outbreaks of cholera were documented against the background of COVID-19 pandemic and laid a double burden on healthcare systems. At the same time, based on the overview of the results of cholera monitoring in the constituent entities of the Russian Federation, it was shown that the forecast of epidemic well-being given for 2021 was fully justified. It has been determined that the increase in the number of non-toxigenic strains of Vibrio cholerae O1 (67) isolated from water bodies compared to 2020 (25) is mainly due to the appurtenance of a number of isolates to clonal complexes. The study of phylogenetic relation has demonstrated that the detection of strains with genotypes which were previously identified in the isolates evidences the persistence potential. The identification of strains with new genotypes, which were earlier established in the strains circulating in other territories, pointed at the possibility of the occasional importations. The forecast of the epidemiological situation on cholera in Russia for 2022 is associated with the continuous existence of risks of introduction. If these epidemiological risks are not realized, a favorable epidemiological situation is predicted regarding this infection in the country. It is expected that the detection of epidemiologically insignificant strains of V. cholerae O1 in environmental water bodies, along with their clones and/or clonal complexes, will remain, including strains that may be an etiological factor in sporadic cases or outbreaks of disease.